Scene and Surface in the Cinema : Implications for Realism - Anderson, Joseph (Cinémas)

(untitled) (Cinémas, 2002)
ABSTRACTThe visual array of a motion picture contains two separable sets of information, one for a three-dimensional diegetic event (scene) and another set of information which specifies the two-dimensional screen upon which the film is projected (surface). The author and his colleagues of the Digital Arts and Imaging Lab have attempted to sort out which information is seen as part of the scene and which as part of the surface. Based on the works of James J. Gibson, their conclusions question the application of the theory of realism to films.